Strategi Pembelajaran Eyl (English For Young Learners) Di Sekolah Dengan Metode Song And Games - Mutiara sofa (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2018)
This paper explains about learning English in school using the song and games method. Learning English in schools is designed to develop English language skills (speaking, writing, listening, and reading) together with activities that are very varied, fun and creative. The Song and Games Method is one of the strategies that can be used in learning English especially for EYL (English for Young Learners). Student's enjoyment in learning English cannot be separated from the teacher's role, the methods and strategies used and the supporting materials. Based on the applicable curriculum, it is always expected to be able to accommodate all material simply, communicatively, activate students' basic thinking patterns, make it easier for teachers to use the Song and Games method, and make students happy learning English. Song (Song) is a series of words that are sung with a certain rhythm and tone. By singing a song, the teacher invites students to do activities that have something to do with everyday life. Games (games) are activities carried out based on certain rules. Children learn through games, when they play together, children interact with one another. In these interactions, language skills can be developed, especially listening and speaking. Very effective English learning strategies for beginners (English for young learners).